Penerapan Perilaku Keberagamaan dalam Aktivitas Berdagang dan Dampaknya terhadap Peningkatan Usaha Pedagang di Sulawesi Selatan - Nurazizah Nurazizah; Sakaria Sakaria; Irfan Yahya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Trading activities are part of the social life of the trading community which involves continuous social and economic interactions, so that the behavior adopted by the trading community has the potential to influence ongoing business dynamics. This research aims to analyze the impact of the religious behavior of the trading community on increasing the business of traders. The research method used is literature study with a qualitative approach. The results of the research show that the implementation of religious behavior in the trading community generally has a positive impact on increasing the business of traders. This impact is reflected in increased buyer trust and loyalty, increased consumer buying interest, the establishment of harmonious social relations, increased economic prosperity of traders, the creation of healthy competition, increased profits of traders, increased business prosperity, and maintained business sustainability in the long term. Overall, this research concludes that the application of religious behavior in trading activities not only provides social capital for the trading community, but also has a positive impact on improving merchant businesses which is reflected through strengthening social relations, business sustainability and business development in the long term. Keywords: Religious Behavior, Increasing Trader Business, South Sulawesi